Strawberry Stock and Order Management System - Ahmad Fadzil, Nur Afrina Fasihah; Aman, Hannani (Applied Information Technology And Computer Science, 2025)
Agricultural and retail industries depend on efficient stock and order management to maintain efficient operations, reduce waste, and satisfy customer requests. The Strawberry Stock and Order Management System was created to reduce the drawbacks of manual inventory tracking and order processing, such as ineffective stock prioritization that causes spoiling and waste and order fulfillment delays, to improve operational efficiency at Mr. Khaw's strawberry farm in Cameron Highlands. To accelerate job execution, the system organizes its components as interactive objects by utilizing Object-Oriented Analysis and System Design (OOASD). Barcode-based inventory management, cross-docking order priority, real-time data processing with FIFO inventory updates, and comprehensive reports are some of the main features. This integration provides useful, data-based information to enhance well-informed decision-making, increases production capacity, and lowers human error. In the end, the system serves as an example of how contemporary technology may revolutionize agricultural operations by enhancing precision, effectiveness, and general output. To further increase the system's intelligence and accessibility, future works might concentrate on automated restock alerts, multilingual support, advanced analytics, mobile optimization, and external platform integration.